Book Review: Malaysian Taxation by Chin Yoong Kheong - Teo, Keang Sood (Journal of Malaysian and Comparative Law, 2019)
Malaysian Taxation, authored by Mr. Chin Yoong Kheong, a chartered accountant and certified public accountant, is to be welcomed.